Effect of Two Different Diets on Growth Performance and Carcass Composition in three Tilapia Strains - N, Eriyusni; T.K, Mukherjee; I, Noraida (Malaysian Journal of Science, 2008)
Effect of diet on the growth performance of three strains of Tilapia; O. niloticus local, O. niloticus philippines and O. mossambicus was investigated. The experimental feed, university feed (UF) contained an energy: protein ratio of 150:1 and was formulated to be isonitrogenous (20% crude protein) and isoenergic (3000 Kcal/kg) compared to that of commercial feed (CF). Fishes were fed with the two experimental diets when they were 10 weeks old at 1.5 x maintenance metabolisable energy for a total period of 32 weeks. Data were analyzed using ANOVA to estimate differences between strains, diets and strain x diet interaction. Mean body weight achieved at the end of the feeding trial with UF vs CF for O . niloticus, O. ossambicus, and O. niloticus philippines were 92.48 ± 4.80g vs 62.82 ± 1.80g, 72.94 ± 1.84g vs 45.82 ± 1.70g and 90.33 ± 2.22g vs 45.82 ± 1.70g, respectively. Feed consumption and feed conversion ratio of strains fed with UF were found to be better than when the fishes were fed with CF. Interaction effect of diet x strain was significant (P < 0.001) for body weight and feed consumption but not for feed conversion ratio. O. niloticus strain was better than O. mossambiclls for body weight and most carcass traits, when analyzed separately for males and females.